Accelerating Economic Development: Resource-Based View and Value Creation at Village Level - Muhammad Gunawan Alif, Christian Haposan Pangaribuan, Maria Wahyuni, Adler Haymans Manurung (International Journal of Advanced Science and Technology, 2020)
As one of the emerging countries in the world, Indonesia’s economic development in cities and urban centers are beginning to display marks of affluence. However, it is not always the same in the rural areas. Using the platform of Resource-Based View and Service Dominant Logic, this exploratory study utilizes focus group discussions and in-depth interviews with successful rural migrants with the objective to get insights on how to accelerate economic development at village level. This study concludes that in order to accelerate economic development at village level, they are encouraged to start with their resources and capabilities, and then innovatively crafted value creation and enhancement based on resources they have. It is very crucial to develop social-economic infrastructure to the market that will only happen with the involvement of all village institutions, both formal and informal.